Status and Distribution of Indian Gaur (Bos gaurus) in Reserved Forests of Tiruchirappalli, Tamil Nadu, India - Griffith Michael G.; Joonu J. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The importance of assessing the status and distribution of Gaur becomes vital for conservation. The Indian gaur presence and distribution often goes unnoticed in the reserved forests outside the national parks and sanctuaries, these often lead to human animal conflict, hence the study was designed to find the status and distribution of Indian gaur in reserve forest in Tiruchirappalli district, Tamil Nadu. The nocturnal survey and and line transect method was followed in the study, which resulted in overall Gaur abundance in Trichy district of 1.51 individual/km2 within the Reserved Forest Area in the southern ranges of Trichy that is Thuvarankuruchi and Manaparai. The Gaurs often stray into the human settlements in search of water and food which leads to conflicts between gaurs and humans. There is increasing trend of population of Indian gaur hence there is need of conservation measures in highly prone conflicts areas.